RELATIONSHIP ROOMING IN WITH BREASTFEEDING SELF-EFFICACY FOR POSTPARTUM MOTHERS IN THE A PRIVATE HOSPITAL - Marnika, Hero; Novita, Regina Vidya Trias (Journal of Maternity Care and Reproductive Health, 2025)
Rooming-in is hospital care that allows mothers and babies to stay together all day for 24 hours, with rooming- in, mothers will feel closer to their babies and babies are breastfed more often. This study aims to determine the relationship of rooming in with the confidence of breastfeeding mothers in a private hospital. The method is a non-experimental observational analytic research method with a cross-sectional approach. The population in this study was all patients giving birth at a private hospital in the November-December 2024 period, using the Slovin formula to obtain 87 samples. The sample was selected using a purposive technique. Total sampling. Statistical analysis showed a p-value of 0.001, which means that there is a significant relationship between rooming-in facilities and mothers' confidence in breastfeeding (P < 0.05). The results of this study provide an understanding that rooming-in is one of the important factors in supporting successful breastfeeding. The next study should companion the mother to breastfeed in the first time so mothers have self efficacy increase gradually. Suggestions for further research include adding observations of latch-on scores during breastfeeding so that they can complement the mother's skills in sustaining breastfeeding in the first six months to two years.